PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA AJAR INOVASI BERBASIS PJBL DAN GAMIFIKASI PADA SISWA SMP - Nurhana; Norma Nasir (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to develop an innovative learning media called “Detective Data” as a tool to enhance students’ motivation and understanding in learning statistics, particularly the concepts of mean, median, and mode. The development of this media was driven by findings indicating that many students perceive statistics as abstract and uninteresting. Therefore, the Project-Based Learning approach was combined with gamification elements to create an investigative learning experience through real data collection activities and statistical analysis. The research was conducted with 33 eighth-grade students at SMP Negeri 33 Makassar. A descriptive approach with a limited trial was employed, using observation sheets, student response questionnaires, and product assessment rubrics as instruments. The results showed that the use of “Detective Data” successfully increased students’ learning motivation, engagement in the learning process, and their ability to analyze data. The investigative posters produced by students demonstrated a solid understanding of data presentation and statistical analysis. Thus, this media can be effectively implemented as a project-based learning tool for statistics instruction.